The Mediterranean as a Laboratory of Border Externalization: Critical Perspectives from the South - Giglioli, Ilaria; Raeymaekers, Timothy (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
Despite the growing prominence of decolonial approaches to borders and migration, the field of border externalization studies remains in need of a critical re-thinking of its main paradigms in order to move beyond state-centrist, Eurocentric and presentist approaches. Drawing on ethnographic research in the Southern and Eastern Mediterranean, this themed section develops an approach to border externalization grounded in the Global South. In diverse sites such as Morocco, Tunisia, Libya, and Turkey, the papers discuss politics of control and practices or resistance, the multiplication of sites of bordering within the nation-state, the role of global networks of migration management and surveillance, as well as the role of race and migration in the national political debate. Drawing on the field of Critical Border Studies, in particular the concepts of ‘borderscapes’, ‘border entanglements’, and ‘border work’, the papers effectively center the multiple agencies, locations, and scales involved in bordering. They also contextualize border externalization within longer histories of imperialism, colonialism and anti-black racism, and ground their scholarship in participatory and grounded forms of research. Taken in conjunction, the themed section demonstrates the empirical and conceptual innovations offered by grounded ethnographic research on bordering in the global south.